Diagnostic capabilities of breast scintigraphy and molecular imaging of the mammary glands in the detection of various biological subtypes of breast cancer - N. S. Popova; S. N. Novikov; P. I. Krzhivitskiy; L. A. Zhukova; P. V. Krivorotko; A. S. Artemyeva; A. E. Michnin; A. A. Valitova; V. V. Danilov; A. V. Chyornaya; T. T. Tabagua; Zh. V. Bryantseva; et al. (ABV-press, 2022)
Background. The accurate and early diagnosis of breast cancer can improve efficacy of the treatment. The standard diagnostic methods such as mammography, ultrasound, and magnetic resonance tomography have a pivotal role in the detection of breast tumors, however, in some cases, they have low diagnostic accuracy. Mammoscintigraphy (MSG) / molecular breast imaging (MBI) with tumor-specific radiopharmacy 99mTc-Technetril in patients with breast cancer can considerably increase the accuracy of diagnosis. However, the diagnostic performance of MSG / MBI in the detection of different biological subtypes of breast cancer is still under investigation.Aim. To evaluate the accuracy of MSG / MBI with 99mTc-Technetril in diagnosis of different biological subtypes of breast cancer.Materials and methods. The analysis included the results of MSG / MBI of 1080 patients (2154 mammary glands), who were examined for suspected breast cancer. MSG / MBI were performed 5-15 min after intravenous injection into the vein of one of the feet of 370-740 MBq of tumor-specific radiopharmacy 99mTc-Technetril. Examinations performed from 2007-2020 was carried out on the emission computed tomography Forte (Philips); since 2020 the molecular visualization has been providing on the special gamma-camera Discovery NM750b (General Electric). The obtained data were evaluated by 2 experienced radiologists. Verification of changes in breasts was provided by morphological examination (1060 cases) or dynamic observation.Results. The sensitivity, specificity and overall accuracy of MSG / MBI were 90 %, 98 %, 95 % correspondingly. When diagnosing tumors with a diameter of up to 10 mm, the sensitivity of MSG / MBI was decreased to 83 %. In patients with various biological subtypes, the sensitivity of MSG / MBI was as follows: luminal A - 88 %; luminal B- - 91 %; luminal B+ - 92 %; triple negative - 93 %; HER2-positive - 96 %. The intensity of tumor uptake depended on the biological subtype of breast cancer. The average values of the 99mTc-Technetril uptake coefficient were as follows: luminal A - 1.59; luminal B- - 1.71; luminal B+ - 1.95; triple negative - 1.93; HER2-positive - 2.22.Conclusion. Retrospective analysis indicate high diagnostic performance of MSG / MBI: sensitivity - 90 %, specificity - 98 %, accuracy - 95 %. There are significant differences in the intensity of 99mTc-Technetril accumulation in tumors in patients with different biological subtypes of breast cancer (p = 0.01-0.004). MSG / MBI characterized by significant differences in the sensitivity in the diagnosis of luminal A and HER2+ breast cancer subtypes: 88 % and 96 %, respectively (p = 0.02).